1959
DOI: 10.1017/s0074180900050786
|View full text |Cite
|
Sign up to set email alerts
|

The transverse motions of the sources of solar radio bursts

Abstract: Observations of the spectrum of solar radio bursts at meter wavelengths have indicated the desirability of measuring positions on the sun's disk not only as a function of time but also as a function of frequency. With this objective in view, we are now using a swept-frequency interferometer to determine the east-west disk coordinate of the transient solar sources at time intervals of £ second and freqency intervals of about 5Mc/s within the frequency range 40 to 70 Mc/s. The accuracy to which the centroid of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

1959
1959
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 6 publications
0
22
0
2
Order By: Relevance
“…Such a procedure will not yield reliable results, since the coronal density varies with time, particularly above sunspots. Indeed, Wild, Sheridan, and Trent (1959) have recently measured the direction of arrival of the different frequencies in type II bursts and have shown that, while the results qualitatively support the plasma hypothesis, they require the scale of the corona to be several times greater than in the conventional models. However, in the absence of detailed knowledge of the electron densities in the corona, it appears worth while to discuss the drift rates in terms of an averaged model, whilst bearing in mind that the results may be correct to order of magnitude only.…”
Section: The Rates Of Frequency Drift and The Inferred Speedsmentioning
confidence: 95%
See 2 more Smart Citations
“…Such a procedure will not yield reliable results, since the coronal density varies with time, particularly above sunspots. Indeed, Wild, Sheridan, and Trent (1959) have recently measured the direction of arrival of the different frequencies in type II bursts and have shown that, while the results qualitatively support the plasma hypothesis, they require the scale of the corona to be several times greater than in the conventional models. However, in the absence of detailed knowledge of the electron densities in the corona, it appears worth while to discuss the drift rates in terms of an averaged model, whilst bearing in mind that the results may be correct to order of magnitude only.…”
Section: The Rates Of Frequency Drift and The Inferred Speedsmentioning
confidence: 95%
“…However, as already indicated, the velocities inferred from the Baumbach-Allen model are almost certainly low by a factor ",,2, so that the agreement is considerably better than is suggested by these figures. Indeed, it may not be too optimistic to hope that the direct measurements of the motion of the sources of type II bursts now being made by Wild, Sheridan, and Trent (1959) may make it possible to associate a particular magnetic storm with a particular type II burst.…”
Section: · ·mentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related to the type III burst are type V bursts, classified due to their long durations (minutes) and wide spectra (Wild et al, 1959). The type V emission appears as a continuation of a type III burst in the dynamic spectra.…”
Section: Type V Burstsmentioning
confidence: 99%
“…The sample of events selected for analysis contains only one burst exhibiting rapid initial movement, but the absence of any systematic variation of position with frequency is characteristic also of the "moving" type IV bursts (see also Wild, Sheridan, and Trent 1959).…”
Section: (B) Variation Of Position With Frequencymentioning
confidence: 99%